Clinical profile and quality of life of patients with occupational contact dermatitis from New Delhi, India. (20th May 2015) - Bhatia, Riti; Sharma, Vinod K.; Ramam, M.; Sethuraman, Gomathy; Yadav, Chander P.
Summary Background Data regarding occupational contact dermatitis (OCD) and its effect on quality of life (QOL) in India are limited. Objectives/aims To evaluate patients with OCD and record the outcome of treatment. Patients/materials/methods All patients with OCD were evaluated for severity of disease (by the use of physician global assessment) and its effect on QOL (by use of the Dermatology Life Quality Index) questionnaire) at the first visit and after 3 months of treatment. Results Among 117 patients with OCD, hand eczema was present in 81.2%. Positive patch test reactions were found in 76%. The most common allergens were Parthenium hysterophorus and potassium dichromate. The most frequent diagnosis was occupational allergic contact dermatitis (OACD) (57%), caused by farming and construction work, followed by occupational irritant contact dermatitis (OICD) (24%), caused by wet work. Severe psychosocial distress was recorded in 62.5% of patients. After 3 months of treatment, 83% improved significantly, and 54% had improvement in QOL. Conclusions Farmers were most frequently affected, followed by construction workers and housewives. OACD was found at a higher frequency than OICD. The most frequent allergens were Parthenium hysterophorus in farmers, potassium dichromate in construction workers, and vegetables in housewives. OCD has a significant impact on QOL. Patch testing, in addition to standard treatment, improves the outcome considerably.